Triterpenoids from the leaves of Abies koreana and their biological activities. (April 2023) - Lee, Dong Jun; Hong, Seong-Min; Yoon, Da Hye; Ham, Song Lim; Kim, Jonghwan; Kim, Sun Yeou; Choi, Sang Un; Kim, Chung Sub; Lee, Kang Ro
Abstract: Seven undescribed triterpenoids, abikoranes A–G, along with three known triterpenoids were isolated from the leaves of Abies koreana E. H. Wilson. The structures of compounds were elucidated by 1D and 2D NMR, HRMS, ECD, specific rotation, and DP4+ analysis. Abikorane A represents the second example of nor-3, 4- seco -17, 14- friedo -lanostane triterpenoid. Among the isolates, some compounds showed strong cytotoxic activities against some of four tested cancer cell lines (A549, SK-OV-3, SK-MEL-2, and HCT-116) with the values of IC50 0.89–9.62 μM, inhibited lipopolysaccharide-stimulated nitric oxide production with IC50 values of 11.57–15.16 μM, and exhibited significant nerve growth factor release effect (192.54 ± 12.33%) from C6 glioma cells. Graphical abstract: Cytotoxic, anti-inflammatory, and neurotrophic triterpenoids were isolated and structurally characterized from Abies koreana. Image 1 Highlights: Seven undescribed triterpenoids were isolated from the twigs of A. koreana. The structures were elucidated by NMR, HRMS, and computation. Abikoreane A have a nor-3, 4- seco -17, 14- friedo -lanostane triterpenoid scaffold. Some compounds showed cytotoxic, anti-inflammatory, and/or neurotrophic activities.